Uso do bagaço de caju como fertilizante em pomar de cajueiro estabelecido - Queiroz, Ronialison Fernandes (2013)
Organic, domestic and industrial residues have recently been used as agricultural fertilizer, providing many advantages such as minimizing the problem of garbage left in the open or in controlled landfills, increasing the usage period of the landfills as well as increasing the nutrients recycling, besides improving the productivity and sustainability of agricultural systems. However, evaluation studies of residues and their effects on the soils, mainly concerning the maximization of their benefits and environmental problems are meager. The aim of the present study was to assess the potential of industrial residues of cashew apples, with and without mineral fertilization, on the soil fertility, plant production and quality of fruits and apples of cashew nut adult plants in field conditions. The experiment was conducted in an orchard located at the Pacajus County, in the Ceará state (Brazil). Treatments were as follows: five dosages of dried cashew bagasse (metric ton per hectare): 0; 3.3; 6.6; 9.9 and 13.2, corresponding to 0; 5.3; 10.6; 15.9 and 21.4 t ha1 of bagasse before sun drying (equivalent to approximately 38.0% of humidity). Treatments included the presence and the absence of additional mineral fertilizers. The experimental design was in randomized blocks with a factorial of 5x2. The soil chemical analyses were carried out at 6, 12, 18, 24 and 30 months after the bagasse incorporation. Parameters annually assessed were plant production (fruits and apples), chemical composition of leaves and fruits. Results showed increase in concentrations of P, K and H+Al in soil, besides increases of N, P and Zn in leaves. Apples exhibited better quality and the fruit production increased 18 months after the bagasse application. The results showed that the incorporation of bagasse in soil as an organic fertilizer improved the nutritional status of cashew plants, the quality of apples and the productivity in an increasing linear function, although more studies involving higher dosages of bagasse as well as higher number of replications are suggested in order to determine the best economical and physical dosages.